Efficiency of visual selection on lowland rice (Oryza sativa L.) grain yield - dos Anjos Cutrim, Veridiano; Patto Ramalho, Magno Antônio; Marinho Carvalho, Assis (Pesquisa Agropecuaria Brasileira, 1997)
This work was carried out aiming to verify if visual selection among F2 plants is effective based on grain yield; if there are differences among breeder skills; and if the early selection, accomplished by each one of the plants individually, is efficient in improving the performance of families in advanced generations. Three populations from the three-way crosses were used. Eleven breeders varying in their experience on the crop, performed visual selection of individual plants with higher grain yield in F2generation. It was realized that the breeders showed different skillness for visually identifying higher yielding plants; in addition, it was found that such skillness is not associated to the individual's experience to identify the highest yielding plants. The progenies, from visually selected plants in the F2 generation, yielded similarly to the ones obtained randomly, showing that the early selection was not effective.